2006
DOI: 10.1021/nl061705n
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Electrical Characterization of Silver Nanobeams

Abstract: By slowing the rate of atomic addition to singly twinned seeds, we have grown silver nanobeams with lengths of 3-30 mum, widths ranging from 17 to 70 nm, and a width to thickness ratio of 1.4. The well-defined dimensions, smooth surface, and crystallinity of nanobeams make them promising candidates for studying the effects of size on electron transport. With a simple method that allows rapid characterization of single nanobeams, we find that even the thinnest nanobeams largely retain the low resistivity of bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(128 citation statements)
references
References 23 publications
5
118
1
4
Order By: Relevance
“…The increased RF induced heating rates of gold nanoparticles <50 nm in diameter and gold nanoshells 10 15 nm thick can be explained by the higher resistivity of small metal nanostructures compared to bulk metals [10]. Recent studies have shown that the resistivity of silver nanowires 15 nm in diameter is approximately twice that of bulk silver.…”
Section: Resultsmentioning
confidence: 99%
“…The increased RF induced heating rates of gold nanoparticles <50 nm in diameter and gold nanoshells 10 15 nm thick can be explained by the higher resistivity of small metal nanostructures compared to bulk metals [10]. Recent studies have shown that the resistivity of silver nanowires 15 nm in diameter is approximately twice that of bulk silver.…”
Section: Resultsmentioning
confidence: 99%
“…Ag 2 S is a useful semiconductor and solid ionic conductor, conducting both ions and electrons at room temperature; [19][20][21] Ag 2 Se is an important semiconductor with promising thermoelectric properties, large magnetoresistance, and high electrical conductivity; [14b,22] Ag has the highest electrical and thermal conductivity among all the metals. [23] Their 1D nanomaterials are important functional or connecting elements in nanometerscale device fabrication [24][25][26][27] with tremendous applications in electronics. For example, Hasegawa and co-workers [24] have realized atomic switches using Ag 2 S-coated Ag nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a lot of research studies have been focused on the growth and properties of twodimensional silver (Ag) nanomaterials due to their amazing ability to control optical properties and their promising applications in optics, photonics, electronics and biotechnology [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. For example, silver nanostructures melting at a temperature well below the melting point of the bulk metal can be used as conductive fillers in electrically conductive adhesives (ECA) for application in microelectronic packaging [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very essential to develop a simple and effective preparation method of silver nanoparticles with controlled size and * E-mail: wangzsedu@126.com shape [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][18][19][20][21][22]. The methods of synthesis of silver nanostructures mainly include solvothermal/hydrothermal processes [22,25] and, photoinduced [4], seed-mediated growth [3,20,21] as well as template [1,18] methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation